Fish Meal Substitution with Black Soldier Fly Larva on Growth Performance of Female Grower Quail - Mulyono Mulyono; Widiyanto Widiyanto; I. Mangisah; L. Krismiyanto; V.D.Y.B. Ismadi; Dwi Sunarti; Nyoman Suthama (Jurnal Sain Peternakan Indonesia, 2023)
The study aimed to evaluate fish meal substitution with black soldier fly larvae supplemented with 2% Trichoderma culture on female grower performance and carcass traits quail. The materials used were 200 two-week-old female quails with an average body weight of 51.5 ± 7.3 grams. The study used a completely randomized design with five treatments and four replications. The treatments were: BSF0 (100% fish meal), BSF25 (75% fish meal + 25% BSF meal), BSF50 (50% fish meal + 50% BSF meal), BSF75 (25% fish meal + 75% BSF meal) ), BSF100 (100% BSF meal). The BSF meal used was added with 2% Trichoderma culture. The rations were iso-calorie and iso-protein, formulated from yellow corn, soybean meal, fish meal, BSF meal, mineral mix, and Trichoderma culture, with metabolic energy of 2,900 kcal/kg and 24% protein. The data were analyzed using variance analysis to determine if it had a significant effect, then continued with Duncan's Multiple Range Test. The results showed that the treatments were insignificant to the FCR, percentages carcass, and ovaries. Nevertheless, significant to (p<0.05) feed intake, live weight, average daily gain and abdominal fat. The substitution of fish meal with BSF + 2% Trichoderma culture was more than 75% decreased feed consumption which caused a decrease in quail's life weight. According to the carcass traits, the BSF + Trichoderma sp 2% could be used up to 100%. However, based on quail performance, it can be concluded that BSF + 2% Trichoderma sp can be used up to 75% in quail rations without harmful effects.